STUDENTSâ RESPONSES ON ENGLISH DEPARTMENT LECTURERSâ COMPETENCE - Hizriani, Nani; Ramadhanti, Fitri (LET: Linguistics, Literature and English Teaching Journal, 2015)
Lecturers have an important role in students academic achievement. There are a number of qualities and competences required by good lecturers. This research is conducted to find out studentsâ responsesÂ and Â their expectations on English department lecturersâ competence .Â There are ninetyÂ studentsÂ of English Department which are taken from the fourth, sixth and eighthÂ semester studentsÂ involved in this study. Questionnaire,Â Â interview, and documentation are used to gather the data . The result showed that Â studentsâ responses on English Department lecturersâ professional competence isÂ inÂ good catergory with mean score 4.1 and total percentage 82%. Meanwhile, studentsâ responses on English Department lecturersâ pedagogical competence isÂ categorized asÂ good with mean score 4.0 and total percentage 80%.Â Â Most studentsÂ expectÂ that the lecturersÂ comeÂ on time to the class. They also expectÂ thatÂ the lecturers use interesting media in teaching and learning, select appropriateÂ method and technique in teaching,Â and give more feedbacks to the students. They also hope their lecturesÂ provide much time for consultation.